Switchable magnetic bottles and field gradients for particle traps - Vogel, Manuel; Birkl, Gerhard; Quint, Wolfgang; Lindenfels, David-Friedrich von; Wiesel, Marco (Applied physics. B, Lasers and optics, 2014)
Versatile methods for the manipulation of individual quantum systems, such as confined particles, have become central elements in current developments in precision spectroscopy, frequency standards, quantum information processing, quantum simulation, and alike. For atomic and some subatomic particles, both neutral and charged, a precise control of magnetic fields is essential. In this paper, we discuss possibilities for the creation of specific magnetic field configurations which find application in these areas. In particular, we pursue the idea of a magnetic bottle which can be switched on and off by transition between the normal and the superconducting phase of a suitable material in cryogenic environments, for example, in trap experiments in moderate magnetic fields. Methods for a fine-tuning of the magnetic field and its linear and quadratic components in a trap are presented together with possible applications.
Published online: 31 October 2013
Gesehen am 29.10.2020